Working sick and out of sorts: a cross-cultural approach on presenteeism climate, organizational justice and work–family conflict - Ferreira, A. I.; Mach, M.; Martinez, L.; Brewster, C.; Dagher, G.; Perez-Nebra, A.; Lisovskaya, A. (International Journal of Human Resource Management, 2019)
A climate of presenteeism has important effects on employee well-being and the organization itself. Our study, based on surveys of health sector employees in six different countries (Brazil, Ecuador, Lebanon, Portugal, Russia and Spain) examines whether organizational justice plays a mediating role in the relationship between a presenteeism climate in the organization and work–family conflict (WFC). Our results indicate that the perception of organizational justice and the presenteeism climate do influence WFC. Moreover, higher levels of WFC were found in non-Latin countries. This study contributes to the work attendance and life balance field by providing cross-cultural empirical evidence corroborating the effect of justice and presenteeism climate on the WFC.